Reconciliation of Environmental Fiqh in Indonesia Legal System - Lahafi, Fikri; Suardi Wekke, Ismail; Muhamaddun, Muzdalifah; ., Rahmawati (Opción, 2019)
This study demonstrates the issues reconciliation of environmental fiqh in Indonesian legal system through the qualitative research, normative-theological and sociological approach. The results of the substance of the Qur’an relating to environmental fiqh is placing humans as caliph in managing the biotic and abiotic environment, there are many verses related the earth and all its contents to preserve, benefit and it can be controlled by humans without exploration and destruction of this nature. In conclusion, the changes of paradigm in environmental fiqh can encourage awareness of society to put pressure to the environmental crisis.